Surface phonon polariton resonance modulation in wurtzite III-nitride semiconductor system via modification of surface structure and formation of alloy structure. - Ng, Sha Shiong (Universiti Sains Malaysia, 2015)
Surface phonon polariton (SPhP) characteristics of wurtzite III-nitride semiconductors have received considerable attention from the scientific research community. This is attributed to its unique resonant characteristics possess a great potential to be used for various important technological applications.